How frontline healthcare workers respond to stock-outs of essential medicines in the Eastern Cape - Hodes, R; Price, I; Toska, E; Bungane, N; Cluver, L (Health and Medical Publishing Group, 2017)
Shortages of essential medicines are a daily occurrence in many of South Africa’s public health facilities. This study focuses in greater depth on the responses of healthcare workers to stock-outs, investigating how actors at the ‘frontline’ of public health delivery understand, experience and respond to shortages of essential medicines and equipment in their facilities. Findings are based on focus groups, observations and interviews with healthcare workers and patients, working within a variety of healthcare facilities in the Eastern Cape, as part of the Mzantsi Wakho study. This research revealed a discrepancy between ‘formal’ definitions of stock-outs and their reporting through formal stock-out management channels. Frontline healthcare workers had designed their own systems for classifying the severity of stock-outs, based on the medical technology in question, and their potential to access surfeit stocks from other facilities. Beyond formal systems of procurement and supply, healthcare workers had established vast networks of alternative communication and action, often using personal resources to ensure availability of medication for patients. Stock-outs were only reported when stock-sharing among networks the frontline healthcare workers failed. These findings have implications for understanding available formal data on frequency and severity of stock-outs.